Pengaruh Pemberian Sari Kacang Hijau Terhadap Peningkatan Kadar Hemoglobin Remaja Putri Anemia di MAN Model Manado - Cindy Berliana Diapaty Mayulu; Rahmat Hidayat Djalil; Ismawati Ismawati (STIKES Columbia Asia Medan, 2023)
Iron is a some nutrient deficiency or anemia is a frequent nutritional problem in adolescents, especially the girls. Anemia is a condition in which the hemoglobin level in the blood is less than normal values (12-16 g/dl). One solution to preventing iron deficiency is by administering green bean juice. The aim of this research was to determine the effectiveness of Giving green bean juice on increasing hemoglobin levels in anemic adolescent girls at MAN Model Manado. The research was pre-experiment with a one group pretest-posttest design. The sample taken 16 Subjekts using purposive sampling. Data collection uses observation sheets. The data collected processed using SPSS 16.0. Statistical tests use the Paired Sample T-test with a significance level of ≤ 0.05. The research results obtained a p value = 0.000 (α ≤ 0.05) it means Ha was accepted and giving green bean juice on increasing the hemoglobin levels of anemic adolescent girls in MAN Model Manado Effectiviness. The conclusion based on the research results there were an effect of giving green bean juice on increasing the hemoglobin levels of anemic adolescent girls in MAN Model Manado. Advice to young women to always consume green bean juice to increase hemoglobin levels.